Genetic Diagnosis of Hyperoxaluria Type 3 Patients Using Haplotype Analysis - Sadegh Tavakoli Ataabadi; Leila Behi; Marzieh Mojbafan; Nakysa Hooman (Kidney & Blood Pressure Research)
Introduction: An autosomal recessive hereditary disorder of the glyoxylate metabolism, primary hyperoxaluria (PH), causes an excess of oxalate to be formed in the body. Three genes have so far been found to cause the three forms of PH (I, II, and III). Overall, 10% of PH patients are type III and are caused by a mutation in the HOGA1 gene. Pathogenic variants responsible for the disease have been identified in several populations. In the present study, we are going to genetically analyze 14 Iranian patients who are suspicious of being affected with PH III. Methods: We studied 14 patients from 11 unrelated Iranian families with a clinical diagnosis of hyperoxaluria disease. The kidney stone was detected in all patients. All of them had high levels of creatinine and oxalate in their urine. Sanger sequencing of the HOGA1 gene was performed in all 14 patients. Next-generation sequencing has also been performed on 1 patient who did not have any causative variants in the HOGA1 gene. Results: We identified one homozygous likely pathogenic missense variant in the HOGA1 (c.266G>A). Conclusion: This is the first report of analyzing the HOGA1 gene in Iranian patients suspicious of being affected with hyperoxaluria type III, which can expand our knowledge about this gene and its mutations.